Determination of basic soil properties and shear strength of Pekan soft clay - Mohd Faruq, Sa'adon (2011)
Soft clay soil can be categorized as problematic soil. The low strength and high compressibility characteristics the soil had, are the major reasons why a careful design analysis could be taken for any structure built on it. Due to these problems, soil investigation on the basic properties and shear strength of the soil must be carried out. This soft clay study has contributed to local engineering studies regarding the basic soil properties and shear strength in Langgar and Pahang Tua soil, where both are located in Pekan. Attempts were made to analyze the soil samples in laboratory. Overall, from the basic soil properties results, there are strong potential for the soil in Langgar and Pahang Tua to be concluded as soft clay type of soil. From the requirement set by American Association of State Highway and Transportation Officials (AASTHO), both Langgar and Pahang Tua soil samples have been dominant by clay particles with more than 35% passing the No.200 sieve, which are 52% in Langgar and 57% in Pahang Tua. The natural moisture content in Langgar and Pahang Tua soil samples are each 57% and 48% which are within the range of moisture content for soft clay soil. For atterberg limit results, Langgar has liquid limit of 51% and plastic limit of 26%. For Pahang Tua, the liquid limit and plastic limit result are 58% and 27%. Based on plasticity chart, both Langgar and Pahang Tua have been determined to be plotted as clay with high plasticity. The shear strength test results have clearly shown the weakness of Langgar and Pahang Tua soil which are within the strength of a soft clay. Both Langgar and Pahang Tua have 19.18kPa and 21.11kPa of shear strength. The results that have been determined from this study can give an extra dimension and usage for engineers to use for any preliminary design in the area of Pekan. The results data of the basic soil properties and shear strength could also allow a quick and economic alternative in order to design for construction on soft clay soil.